Histrionic Personality, Narcissistic Personality, and Problematic Social Media Use: Testing of a New Hypothetical Model - Savci, Mustafa; Turan, Mehmet Emin; Griffiths, Mark D.; Ercengiz, Mustafa (Springer, 2021)
In the present study, a hypothetical model examining the relationships between histrionic personality belief, need for social approval, desire for being liked, social media disorder, and narcissistic personality belief was proposed and tested. The effect of histrionic personality belief on the need for social approval and desire for being liked was tested first. Then the effect of the need for social approval and desire for being liked on social media addiction were tested. Finally, the effect of social media addiction on narcissistic personality belief was tested. The present study comprised 305 adolescents (165 girls and 140 boys) and they were administered the Personality Belief Questionnaire-Short Form, Need for Social Approval Scale, Desire for Being Liked Scale, and Social Media Disorder Scale. Before the proposed hypothetical model was tested, each latent variable was tested with measurement models to determine if it could be used in structural models. Findings demonstrated that histrionic personality belief positively affected the need for social approval and desire for being liked. The need for social approval and desire for being liked positively affected social media addiction. Finally, social media addiction positively affected narcissistic personality belief.
Keywords: Social media use; Histrionic personality belief; Need for social approval; Desire for being liked; Social media addiction; Narcissistic personality belief